Management of complications associated with the use of hyaluronic acid fillers. Recommendations of the Aesthetic Dermatology Section of the Polish Dermatological Society - Zegarska, Barbara; Ambroziak, Marcin; Ornatowska, Małgorzata; Barańska-Rybak, Wioletta (Dermatology Review/Przegląd Dermatologiczny, 2020)
The most common treatments in the field of aesthetic dermatology and broadly understood aesthetic medicine are those with the use of fillers. For many, hyaluronic acid injections are considered very safe and the effects predictable. Therefore, the widely recognised reversibility of the effects of hyaluronic acid fillers and the growing variety of approved applications and formulations of these products increase their popularity. There are also numerous undesirable effects and complications, especially due to the fact that these treatments are performed both by unauthorised persons and under inappropriate conditions. Complications may be related to: incorrect injection technique, lack of treatment asepsis, reaction of the body to the presence of a foreign body and anatomical changes. Depending on the time when complications occur after hyaluronic acid administration, following complications may be distinguished: immediately complications that occur immediately or up to 3–5 days after administration are and late complications that occur even after several weeks, months or even years. Non-vascular complications of hyaluronic acid administration are: nodules, granulomas, persistent swelling, Tyndall effect, infections and biofilm. The most dangerous are vascular complications after hyaluronic acid administration, such as: ischaemia/partial or complete necrosis, vision abnormalities and blindness. Early recognition of a complication largely prevents permanent defects. The use of hyaluronidase injections is considered management of choice in the treatment of complications of hyaluronic acid fillers and should be performed immediately after the procedure with the use of the filler. Therefore, it was necessary to develop a consensus on the principles of hyaluronidase administration for complications of hyaluronic acid filler procedures.